2018
DOI: 10.1371/journal.pone.0199357
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of vegetation to climate variability and its implications for malaria risk in Baringo, Kenya

Abstract: The global increase in vector borne diseases has been linked to climate change. Seasonal vegetation changes are known to influence disease vector population. However, the relationship is more theoretical than quantitatively defined. There is a growing demand for understanding and prediction of climate sensitive vector borne disease risks especially in regions where meteorological data are lacking. This study aimed at analyzing and quantitatively assessing the seasonal and year-to-year association between clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
4
19
0
2
Order By: Relevance
“…darlingi breeding [48], while the study conducted by Ssempiira et al that was located in Uganda, observed that the incidence of malaria was increased with day temperature, however very high temperatures above 29 • C resulted in a decline of malaria incidences [37]. This result was concordant with the study of Amadi et al, which was located at Baringo in Kenya and found that average monthly minimum temperatures between 16.2-21 • C (lag 1-month) made favorable conditions for the increase of the malaria risk [84].…”
Section: Predictors For Malariasupporting
confidence: 69%
See 4 more Smart Citations
“…darlingi breeding [48], while the study conducted by Ssempiira et al that was located in Uganda, observed that the incidence of malaria was increased with day temperature, however very high temperatures above 29 • C resulted in a decline of malaria incidences [37]. This result was concordant with the study of Amadi et al, which was located at Baringo in Kenya and found that average monthly minimum temperatures between 16.2-21 • C (lag 1-month) made favorable conditions for the increase of the malaria risk [84].…”
Section: Predictors For Malariasupporting
confidence: 69%
“…Additionally, precipitation proved to be another significant predictor in the tropical zone highly associated with malaria occurrence [35,37,40,84]. Contrariwise, the study of Kabaria et al that was conducted in Tanzania (tropical region) was the only one study that claimed precipitation performed poorly as a predictor [38].…”
Section: Predictors For Malariamentioning
confidence: 99%
See 3 more Smart Citations